Ignition of Hovering Droplets of Organic Coal Water Fuels; Journal of Engineering Physics and Thermophysics; Vol. 92, iss. 1 - Valiullin T. R. Timur Radisovich; Vershinina K. Yu. Kseniya Yurievna; Medvedev V. V. Valery Vasilievich; Ozerova I. P. Irina Petrovna (2019, 2019)
Title screen